Penerapan Metode Time Series Dalam Forecasting Penjualan Pada “Nasi Goreng Bacot” - Bagas Adil Putrajaya; Agung Brastama Putra; Rizka Hadiwiyanti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The restaurant industry in Indonesia has experienced significant growth, driving the need for data-driven strategies to remain competitive. This study aims to apply and compare time series methods in forecasting sales at